Effects of TiO2 and H2O2 treatments on the biosynthesis of carotenoids and lipids in oleaginous red yeast Rhodotorula glutinis ZHK. (15th April 2023) - Zhao, Die; Li, Chunji
Abstract: Microbial carotenoids and lipids are two groups of versatile biomolecules widely used in the food, fuel, pharmaceutical, and cosmetic industries. Rhodotorula glutinis is one of the best-known oleaginous red yeasts that has the remarkable capability to produce an assortment of valuable carotenoids and lipids. Here, the effects of different concentrations of TiO2 and H2 O2 treatments on carotenoid and lipid production in R. glutinis ZHK were investigated. After 120 h of cultivation, the total amount of carotenoids was significantly increased in the TiO2 (100 mg/L: 23.165 μg/gdw, 750 mg/L: 19.65 μg/gdw) and H2 O2 (5 mM: 21.51 μg/gdw, 10 mM: 118.858 μg/gdw) treatments than the control (6.099 μg/gdw). In contrast, as compared to the control, the relative abundance of total lipids was significantly decreased in the TiO2 (100 mg/L) and H2 O2 (10 mM) treatments, respectively. In response to TiO2 and H2 O2 stresses, the increased carotenoids were probably attributed to the down-regulated lipid biosynthesis flux, while the decreased lipids might be ascribed to the down-regulated fatty acid biosynthesis flux. Our results presented herein not only provide an effective strategy for modulating carotenoid and lipid biosynthesis in R. glutinis ZHK but also reveal the molecular foundation to further enhance their bioproductivity by molecular manipulation. Highlights: Rhodotorula glutinis is a promising source for microbial carotenoid and lipid production. TiO2 /H2 O2 addition promotes carotenoid production but restrains lipid production . TiO2 /H2 O2 addition decreases total biomass and causes high oxidative stress. Multi-omics uncovers the effects of TiO2 /H2 O2 addition on carotenoid and lipid production.